With Our Backs to the Future - Gent, Craig (Identities: Journal for Politics, Gender and Culture, 2015)
“The future has been cancelled,” declares the ‘accelerationist manifesto.’ But where does this lead us? Concepts such as ‘time’ and ‘the future’ are almost ineffably broad once given a degree of sustained concentration. In this essay, I look to the relationship between temporality (as our phenomenological experience of what is to come) and historicity (in the sense of the direction of society) in order to question how our perception of temporality in the everyday conditions our perception of the horizon of possibilities which comprise the future, particularly with regard to conceiving or imagining a future which is non-capitalist. Author(s): Craig Gent Title (English): With Our Backs to the Future Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 49-60 Page Count: 11 Citation (English): Craig Gent, “With Our Backs to the Future,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 49-60.